2005
DOI: 10.1016/j.neuron.2005.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Distribution of EGFR Receptor during Mitosis Generates Diverse CNS Progenitor Cells

Abstract: It has been debated whether asymmetric distribution of cell surface receptors during mitosis could generate asymmetric cell divisions by yielding daughters with different environmental responsiveness and, thus, different fates. We have found that in mouse embryonic forebrain ventricular and subventricular zones, the EGFR can distribute asymmetrically during mitosis in vivo and in vitro. This occurs during divisions yielding two Nestin+ progenitor cells, via an actin-dependent mechanism. The resulting sibling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
143
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 57 publications
17
143
0
1
Order By: Relevance
“…The distinct actions exerted by TGFa on cortical neural progenitors, mitogenic or promoting an astrocytic fate according to the developmental stage, depend on the low or high expression levels of its receptor, respectively. During the late stage of embryonic development, when gliogenesis takes over neurogenesis, it favours the preferential differentiation of neural progenitors into astrocytes over neurons, an effect mediated by enhanced expression of erbB1, and segregation of the receptors into the daughter cell that will ultimately acquire an astrocyte phenotype (Lillien, 1995;Burrows et al, 1997;Sun et al, 2005). Interestingly, we observed that conversion of mature astrocytes into progenitor-like cells correlated with the downregulation of the wholecell erbB1 content, suggesting that modulation of the receptor levels might be part of the mechanisms by which TGFa alters the astrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct actions exerted by TGFa on cortical neural progenitors, mitogenic or promoting an astrocytic fate according to the developmental stage, depend on the low or high expression levels of its receptor, respectively. During the late stage of embryonic development, when gliogenesis takes over neurogenesis, it favours the preferential differentiation of neural progenitors into astrocytes over neurons, an effect mediated by enhanced expression of erbB1, and segregation of the receptors into the daughter cell that will ultimately acquire an astrocyte phenotype (Lillien, 1995;Burrows et al, 1997;Sun et al, 2005). Interestingly, we observed that conversion of mature astrocytes into progenitor-like cells correlated with the downregulation of the wholecell erbB1 content, suggesting that modulation of the receptor levels might be part of the mechanisms by which TGFa alters the astrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…TGFa acts as a mitogenic or differentiating factor at different steps of the pathway leading from a neural stem cell to a mature astrocyte according to the low or high levels of erbB1 expressed by the cell (Lillien, 1995;Burrows et al, 1997;Sun et al, 2005). Any analysis of TGFa effects thus requires a careful characterization of the cell population studied.…”
Section: Introductionmentioning
confidence: 99%
“…This bias toward glial differentiation is attributed to synergistic effects of EGF and LIF (leukemia inhibitory factor) 6. Asymmetric distribution of the EGFR after mitosis of ventricular zone (VZ) and subventricular zone (SVZ) precursors seems to affect cell fate, with a predetermination of the EGFR high population to an astrocytic fate 7. In the adult brain, EGFR has been shown to play a critical role in the regulation of the neurogenic niches, found in the SVZ of the forebrain and the subgranular zone of the hippocampus 8 9 10, where activation of stem cells appears to correlate with the acquisition of EGFR expression 9.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have implicated epidermal growth factor receptor (EGFR) signaling in the migration, proliferation, and differentiation of neural progenitor cells. During embryonic development, EGFR plays a major role in cell migration (Bayer et al, 1991;Burrows et al, 1997Burrows et al, , 2000Caric et al, 2001;Boockvar et al, 2003;Ciccolini et al, 2005), proliferation (Gritti et al, 1999), and differentiation (Lillien, 1995;Viti et al, 2003;Sun et al, 2005), although the effects of EGFR signaling vary with the cell type and developmental time. EGFR-mediated signaling is involved in both radial and tangential modes of migration (Bayer et al, 1991).…”
Section: Introductionmentioning
confidence: 99%